Neighborhood-level socioeconomic factors moderate the association between physical activity and relative age effect: a cross-sectional survey study with Japanese adolescents - Takaaki Mori; Takumi Aoki; Kan Oishi; Tetsuo Harada; Chiaki Tanaka; Shigeho Tanaka; Hideki Tanaka; Kazuhiko Fukuda; Yasuko Kamikawa; Nobuhiro Tsuji; Keisuke Komura; Shohei Kokudo; et al. (BMC, 2022)
Abstract Background Relative age effect is defined as a phenomenon where children born early generally perform better than children born later in the same cohort. Physical activity is an important factor that might be influenced by the relative age effect. Socioeconomic factors (e.g., parent's income, education level) are also associated with the adolescent's physical activity. However, no existing study has examined whether socioeconomic factors moderate the relative age effect on the adolescent's physical activity. This study aims to clarify whether and how birth month and socioeconomic factors relate to organized sports and physical activity among adolescents in Japan. Methods We conducted a questionnaire survey targeting 21,491 adolescents who live in a widespread neighborhood. We included 8102 adolescents (4087 males and 4015 females: mean age 13.1 ± 1.4) in the analysis. Based on the participants' birth months, we divided them into four groups (April to June, July to September, October to December, January to March). We asked participants to report their organized sports participation. Using the International Physical Activity Questionnaire for Japanese Early Adolescents, we identified their moderate to vigorous physical activity (MVPA). Neighborhood-level socioeconomic factors (areal deprivation, average annual income, education level) were analyzed based on national surveys, such as the population census. We performed multilevel logistic and linear regression analysis for organized sports participation and MVPA, respectively. Moreover, a simple slope analysis was implemented if the interaction between birth month and socioeconomic factor was significant in the multilevel linear regression analysis. Results Among males, relatively younger adolescents (adolescents who were born later in the same grade) were less likely to participate in organized sports activites (OR=0.90, 95% CI 0.82-0.97, p<0.05), while both males and females engaged in less MVPA (b=-0.54, b=-0.25, p< 0.01, respectively). We observed an interaction between birth month and socioeconomic factors. Among males in low-income neighborhoods, and females in more deprived neighborhoods, relatively younger adolescents engaged in less MVPA. Conclusions Socioeconomic factors moderate the relative age effect on adolescents' physical activity. The relative age effect on adolescents' physical activity might be more likely to appear among adolescents from socioeconomically disadvantaged neighborhoods.